Effects of intraoperative individualized PEEP on postoperative atelectasis in obese patients: study protocol for a prospective randomized controlled trial - Chen Zhu; Jing-Wen Yao; Li-Xin An; Ya-Fan Bai; Wen-Jing Li (Trials, 2020)
Abstract Background Obese patients undergoing general anesthesia and mechanical ventilation during laparoscopic abdominal surgery commonly have a higher incidence of postoperative pulmonary complications (PPCs), due to factors such as decreasing oxygen reserve, declining functional residual capacity, and reducing lung compliance. Pulmonary atelectasis caused by pneumoperitoneum and mechanical ventilation is further aggravated in obese patients. Recent studies demonstrated that individualized positive end-expiratory pressure (iPEEP) was one of effective lung-protective ventilation strategies. However, there is still no exact method to determine the best iPEEP, especially for obese patients. Here, we will use the best static lung compliance (Cstat) method to determine iPEEP, compared with regular PEEP, by observing the atelectasis area measured by electrical impedance tomography (EIT), and try to prove a better iPEEP setting method for obese patients. Methods This study is a single-center, two-arm, prospective, randomized control trial. A total number of 80 obese patients with body mass index ≥ 32.5 kg/m2 scheduled for laparoscopic gastric volume reduction and at medium to high risk for PPCs will be enrolled. They will be randomly assigned to control group (PEEP5 group) and iPEEP group. A PEEP of 5 cmH2O will be used in PEEP5 group, whereas an individualized PEEP value determined by a Cstat-directed PEEP titration procedure will be applied in the iPEEP group. Standard lung-protective ventilation methods such as low tidal volumes (7 ml/kg, predicted body weight, PBW), a fraction of inspired oxygen ≥ 0.5, and recruitment maneuvers (RM) will be applied during and after operation in both groups. Primary endpoints will be postoperative atelectasis measured by chest electrical impedance tomography (EIT) and intraoperative oxygen index. Secondary endpoints will be serum IL-6, TNF-α, procalcitonin (PCT) kinetics during and after surgery, incidence of PPCs, organ dysfunction, length of in-hospital stay, and hospital expense. Discussion Although there are several studies about the effect of iPEEP titration on perioperative PPCs in obese patients recently, the iPEEP setting method they used was complex and was not always feasible in routine clinical practice. This trial will assess a possible simple method to determine individualized optimal PEEP in obese patients and try to demonstrate that individualized PEEP with lung-protective ventilation methods is necessary for obese patients undergoing general surgery. The results of this trial will support anesthesiologist a feasible Cstat-directed PEEP titration method during anesthesia for obese patients in attempt to prevent PPCs. Trial registration www.chictr.org.cn ChiCTR1900026466. Registered on 11 October 2019